Inclusive Healthcare Facilities Management: Case Study Approach - Nuratiqah Aisyah Awang,; Shirley Jin Lin Chua,; Azlan Shah Ali, (2025)
This study examines how adopting an inclusive approach to facilities management (FM) can better meet the needs of Persons with Disabilities (PWDs) in government hospital buildings across Malaysia. While the Persons with Disabilities Act 2008 was introduced to ensure equal access to public services for PWDs, various barriers—including societal attitudes and physical limitations within the built environment—have continued to hinder their full participation in society.Previous research has highlighted a major concern: the gradual decline in facility quality due to inadequate maintenance, which significantly impacts PWDs users. To address this issue, the study employs a mixedmethods approach, combining questionnaire surveys with semistructured interviews, to explore ways to improve the management of PWD-related facilities.Findings indicate that services for PWDs often fall short of expectations, with many relevant facilities neglected during routine maintenance. Notably, PWD-specific features are frequently absent from Preventive Planned Maintenance (PPM) checklists and are rarely considered in performance evaluations. Inspections tend to be general in nature, relying heavily on inspectors’ discretion rather than focused assessments of PWD needs.Although complaints about PWD facilities represent a small portion of total reports, they are often critical, especially concerning safety, accessibility, and usability. These issues typically stem from poor maintenance and are exacerbated by difficulties in accessing information and using the facilities effectively. In response, the study proposes a dedicated maintenance guide to strengthen current management strategies. This guide aims to improve the upkeep and performance of PWD facilities in government hospitals, fostering a more inclusive environment for all users.